Association between NOD2 single nucleotide polymorphisms and Grade III–IV acute graft-versus-host disease: A meta-analysis. Issue 5 (June 2015) - Zhao, Haizhao; Jia, Ming; Wang, Zhujun; Cheng, Yuping; Luo, Zebin; Chen, Yuanyuan; Xu, Xiaojun; Yang, Shilong; Tang, Yongmin
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives The effects of NOD2 single nucleotide polymorphisms (SNPs) on Grade III–IV acute graft-versus-host disease (aGVHD) risk are somewhat contradictory in different studies. The aim of the meta-analysis was to clarify the effects of NOD2 SNPs on the incidence of Grade III–IV aGVHD. Methods We searched PubMed, EMBASE, Web of SCIENCE, WanFang and Chinese National Knowledge Infrastructure (CNKI) databases to collect eligible publications. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to assess the association between NOD2 polymorphisms and Grade III–IV aGVHD risk. Results A total of nine studies from eight publications met the inclusion criteria and were included in this meta-analysis. Patient NOD2 SNPs were not associated with aGVHD risk. A tendency of higher risk to develop Grade III–IV aGVHD was found in patients with pairs NOD2 SNPs. Subgroup analyses showed that pairs NOD2 SNPs were associated with Grade III–IV aGVHD in the Caucasian population and in identical sibling donors (IS), but not in matched unrelated donors (MUD). In patients who received hematopoietic stem cell transplantation (HSCT) with T-cell depletion and gut decontamination, there was still an association between pairs NOD2 SNPs and Grade III–IV aGVHD risk. Conclusions Our meta-analysis suggests that pairs NOD2 SNPs, not patient NOD2 SNPs, may be associated with Grade III–IV aGVHD risk, especially in the Caucasian population. It is also indicated that in pairs NOD2 polymorphisms group, patients who receive HSCT from IS may experience higher risk of Grade III–IV aGVHD.